(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to identify the impact of entrepreneurial thinking on reducing organizational aging. As organizations mature, they often face challenges related to bureaucratic structures, resistance to change, and declining innovation. Entrepreneurial thinking has been proposed as being of paramount importance in the modern business environment. It refers to the ability to identify market opportunities and discover the most appropriate ways and times to capitalize on them. This mindset is not limited to entrepreneurs; anyone can benefit from adopting this perspective, whether they are working in an entry-level position, mid-career in a large company, or starting out on their own. The current study uses an analytical survey methodology to explore how entrepreneurial thinking initiatives within organizations contribute to mitigating the negative effects of aging. To achieve the study objectives, the researcher distributed a questionnaire to workers in the men’s clothing factory in Najaf Governorate. (368) responses were obtained and analyzed using the advanced statistical program SmartPLS V.4. The research reached a set of conclusions, the most important of which are: Entrepreneurial thinking may contribute to strategic renewal within organizations. This includes making a deliberate effort to re-evaluate and revitalize the organization’s strategy, structure, and operations. Strategic renewal can resist the entrenchment of outdated practices, thus reducing organizational aging. A set of recommendations were also presented, the most important of which are: the need to embrace technological developments related to the men’s clothing industry. This includes adopting modern production methods, integrating automation, and using data analytics to make informed decisions and maintain competitiveness in the market.